Strain dependence electrical resistance and cohesive strength of ITO thin films deposited on electroactive polymer - Rebouta, L. (2010)
Transparent, conducting, indium tin oxide (ITO) films have been deposited, by pulsed dc magnetron sputtering, on glass and electroactive polymer (poly(vinylidene fluoride)-PVDF) substrates. Samples have been prepared at room temperature by varying the oxygen partial pressure. Electrical resistivity around 8.4 x 10(-4) Omega cm has been obtained for films deposited on glass, while a resistivity of 1.7 x 10(-3) Omega cm has been attained in similar coatings on PVDF. Fragmentation tests were performed on PVDF substrates with thicknesses of 28 mu m and 110 mu m coated with 40 nm ITO layer. The coating's fragmentation process was analyzed and the crack onset strain and cohesive strength of ITO layers were evaluated.